2015
DOI: 10.1007/s00701-015-2639-6
|View full text |Cite
|
Sign up to set email alerts
|

Promising clinical outcome of elderly with TBI after modern neurointensive care

Abstract: The outcome of elderly patients with TBI was significantly worse than in younger patients, as expected. However, as much as 51 % of the elderly patients showed a favorable outcome after NIC. We believe that these results encourage modern NIC in elderly patients with TBI. We need to study how secondary brain injury mechanisms differ in the older patients and to identify specific outcome predictors for elderly patients with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
1
11
0
2
Order By: Relevance
“…The main cause of trauma in all elderly age groups was fall (Table 1 ), which is in accordance with our earlier findings [ 22 , 28 ] as well as with the results of many other studies [ 8 , 15 , 17 , 19 , 23 , 34 , 36 , 40 ]. Although there was a predominant injury mechanism, there was a notable significant difference between the age groups regarding several other characteristics (Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The main cause of trauma in all elderly age groups was fall (Table 1 ), which is in accordance with our earlier findings [ 22 , 28 ] as well as with the results of many other studies [ 8 , 15 , 17 , 19 , 23 , 34 , 36 , 40 ]. Although there was a predominant injury mechanism, there was a notable significant difference between the age groups regarding several other characteristics (Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…An updated periodic evaluation of NIC of TBI patients made by us showed substantial increase of the proportion of patients > 60 years treated from 16 to 30% between 1996–1997 and 2008–2009 [ 22 ]. Furthermore, when clinical outcome was evaluated in the elderly TBI patients who received NIC, 51% of patients age ≥ 65 had favorable outcome [ 28 ]. Those relatively favorable results indicate that elderly patients with TBI should not be excluded from NIC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…151,152 Regardless of the presence or absence of an inflection point, it is clear that a substantial number of older adults with TBI may recover well ( Table 1, Table 2, and Supplementary Table; see online supplementary material at http://www.liebertpub .com/neu), including some with severe TBI who receive aggressive neurosurgical management. 29,92,138,[153][154] The role of provider attitudes as well as patient and family preferences must also be considered when interpreting outcomes in older adults with TBI, who may be more likely to have care electively withdrawn. 155 The issue of provider attitudes was highlighted in a large UK study of patients with TBI and cerebral contusions, reporting that increasing age was associated with longer delays in obtaining an initial head CT, lower likelihood of being transferred to a neurotrauma center, and lower likelihood of review by a senior (vs. junior) physician.…”
Section: The Controversial Role Of Agementioning
confidence: 99%
“…For instance, elderly TBIs are at greater risk of worse functional recovery than younger TBI patients (McIntyre et al, 2013). However, in literature, studies are showing that elderly TBI patients respond well to neurosurgical treatment and rehabilitation, suggesting that chronological age alone is not an adequate indicator of prognosis (McIntyre et al, 2013;Merzo et al, 2016). For this reason, it has been suggested that additional prognostic factors, such as MCs, should be considered when evaluating the clinical evolution of elderly TBI patients (Estraneo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%